Base editors in zebrafish: a new era for functional genomics and disease modeling - Liu, Yuwen; Li, Chao; Qiu, Yiren; Chen, Sihong; Luo, Yijun; Xiong, Donghua; Zhao, Jun; Ye, Jianmin; Wang, Xuegeng; Qin, Wei; Liang, Fang (Frontiers in Genome Editing, 2025)
Base editing has revolutionized genome engineering by enabling precise single-nucleotide modifications without inducing double-strand breaks. As a powerful and efficient gene-editing tool, base editors (BEs) have been widely applied in various model organisms, including zebrafish (Danio rerio), to facilitate functional genomic studies and disease modeling. Zebrafish, with its genetic similarity to humans and rapid development, provides an excellent platform for testing and optimizing emerging base editing technologies. This review comprehensively explores the advancements of cytosine and adenine base editors in zebrafish, highlighting recent developments that enhance efficiency, specificity, and editing scope. We discuss novel base editor variants tailored for zebrafish applications, improvements in delivery strategies, and methodologies to minimize off-target effects. Furthermore, we compare base editing with other precision genome-editing technologies, such as prime editing and homology-directed repair, to underscore its advantages in achieving targeted mutations with high fidelity. By evaluating the expanding role of base editing in zebrafish, this review provides valuable insights into its potential for translational research, genetic disease modeling, and future therapeutic applications.